Experience with laparoscopic common bile duct exploration in failed endoscopic retrograde cholangiopancreatography cases at a tertiary care hospital - Panwar, Pradeep; Reddy, Hetish M.; Bagree, Rajendra; Jalendra, Gaurav (International Surgery Journal, 2020)
Background: Minimally invasive techniques for stone removal in common bile duct (CBD) are endoscopic retrograde cholangiopancreatography (ERCP) followed by laparoscopic cholecystectomy (LC) or laparoscopic CBD exploration with LC (laparoscopic common bile duct exploration (LCBDE) and LC). Failed, multiple attempted or complications of ERCP leads to other surgical approaches where LCBDE is a preferable option by experts due to its added benefits. Methods: We did LCBDE and LC in 40 cases of failed ERCP. Standard investigation protocol was followed in all cases and CBD were explored laparoscopically and stones were retrieved. Post retrieval choledochoscopy was done and sphincter of oddi was dilated by the dilators. Results: With careful selection of cases, stone calculi were retrieved successfully in 38 cases by laparoscopically and 2 cases by open method after conversion. Postoperative choledochoscopy were found normal. Bile leak seen in 3 cases, which were managed conservatively. Standard regime of postoperative care was taken followed by T-tube removal after cholangiogram on day 10-14. All patients survived the operation. Conclusion: We advocate that LCBDE is the most viable alternative for open surgery in failed ERCP cases for retrieval of CBD stones. This results in early recovery, better cosmetic scar, least complications with early resumption of routine life. Needs cautious patient selection and expertise in laparoscopic surgery.